Design, Research and Practical Implementation of the Laser Shooting Simulation System for 5.56 mm G-36, 7.62 mm FN MAG and 84 mm Carl Gustaf - Algimantas FEDARAVIČIUS (Wojskowa Akademia Techniczna, 2016)
Riflemen’s trainers are efficiently applied for the training of the armed forces, police, and shooting sportsmen. However, the training quality directly depends on the perfection of trainers as well as on their functional facilities. One of them is the shooting possibility by using various weapons. The new modification of a practise range is created: it’s included three types of weapons imitators for 5.56 mm G-36 assault rifle, 7.62 mm FN MAG machine gun and, 84 mm CARL GUSTAF recoilless gun. The work presents the universal dynamical and mathematical models of the one way operation pneumatic drive for recoil imitation, results of its investigation and description of the new modification of laser range for riflemen.
Keywords: Laserowy system symulacji strzału